Effects of haruan pressurized in water extract on SK-N-SH human neuroblastoma cell line in vitro - Ibrahim, Buhari (2015)
Effects of haruan pressurized in water extract (HPIWE) on SK-N-SH neuroblastoma cell line was studied in vitro. MTT assay, phase contrast microscopy and flow cytometry were employed to evaluate the effects of HPIWE on SK-N-SH cells. To start with, MTT assay was run to observe the effect of the haruan extract on cell viability of SK-N-SH human neuroblastoma cells. The cells were treated with various concentrations of the HPIWE to undertake a first step in screening the extract for its cytotoxic effects. The result showed the cell viability of 68.8 % at the highest concentration of 100 μg/m, indicating that HPIWE possesses no cytotoxic effect because no IC50 could be determined. Another MTT assay was run with 250 μg/ml of the extract as highest concentration to observe if increasing the concentration will produce better result. However, the result indicates about 72% cell viability of the SKN-SH cells. Therefore, since 100 μg/ml produces less viability,it was adopted for subsequent experiments. This concentration was then used to study the effects HPIWE on cellular morphology of the SK-N-SH cells using phase contrast microscope. No alteration of cellular morphology was observed on SK-N-SH cells as compared to the control cells which did not receive treatment. Based on the MTT assay and the morphological studies by phase contrast, there were no observable effects of the HPIWE on SK-N-SH cells. Our study further search for the apoptotic effects of the extract using ApoBrdU in situ DNA fragmentation assay kit followed by quantification of the DNA strand break using flow cytometry. One-way ANOVA test was used to compare the difference between the treated cells and the control cells (untreated cancer cells). The analysis showed that the HPIWE induced apoptosis in a time dependent manner and significant value (*p< 0.05) was obtained when compared with the control. The result confirmed that the HPIWE induced apoptosis on the SK-N-SH human neuroblastoma cancer cells. However, the amount of cells that underwent apoptosis were less than 50% of the total cells, meaning that even from the flow cytometry result,no IC50 could be generated. Therefore, the result of flow cytometry could be correlated with the MTT assay result, because in both assays, over 30% of cell death was recorded. However, the overall result of the study showed that HPIWE was not an effective anti-proliferative agent on SK-N-SH cells. Therefore, further studies should target the use of non-polar haruan extract for cancer related studies. Also angiogenesis and cell migration assay should be used to demonstrate the effect of HPIWE on brain cancer and or other cancer cell lines.